Redox and solvent-stable alkaline serine protease from Bacillus patagoniensis DB-5: heterologous expression, properties, and biotechnological applications - Li, Zhimin; Xing, Yanmin; Liu, Pulin; Liao, Weifang; Miao, Lihong (Frontiers in Microbiology, 2025)
The aprBP gene from Bacillus patagoniensis DB-5, encoding a 378-amino-acid alkaline protease, was cloned and expressed in Escherichia coli. The amino acid sequence of APrBP showed 62.8–84.4% identity with the S8 peptidase subtilisin family alkaline proteases reported in the literature. Recombinant APrBP was purified using Ni-NTA affinity chromatography with 45.61% recovery and a homogeneous band was detected at approximately 38 kDa on the SDS-PAGE gel. The optimum temperature of APrBP was 60°C. The presence of 2 mM Ca2+ significantly enhanced the optimal temperature and thermostability. The enzyme demonstrated optimum activity at pH 12 and maintained high stability at pH 8.0–11.0. Protease activity was stimulated by Mn2+, Ca2+, Mg2+, Ni2+, TritonX-100, Tween-20 and Tween-80, while completely inactivated by PMSF, EDTA and Cu2+. The APrBP exhibited good tolerance to oxidizing and reducing agents. Notably, the protease exhibited remarkable stability in 50% (v/v) concentrations of several organic solvents, such as methanol, acetone, glycerol, dimethyl sulfoxide, n-hexane, and ethyl acetate. The APrBP efficiently hydrolyzed natural proteins, demonstrating the highest catalytic efficiency for casein, excellent hydrolysis activity for bovine serum albumin, hemoglobin, and keratin, and favorable hydrolysis ability for whey proteins. Moreover, molecular docking results revealed stable interactions between APrBP and casein, hemoglobin, whey proteins and keratin. This study indicated that APrBP has some useful properties and explored its potential as a bio-additive detergent as well as in utilizing feather waste and whey protein.